Elephant Towers and Tower of the Sun, Reflected in the Waters of San Francisco Bay, California World's Fair on San Francisco Bay (Stanley A. Plitz Company)
Two massive Elephant Towers flank the Portals of the Pacifica - the main entrance to the Fair. The Towers are 120 feet high and are sumounted by three elephant motives, - age-old symbols of pageantry. In the background, is the magnificent gleaming 400 foot Tower of the Sun.